PENERAPAN TANGGA NADA MINOR MELODIK DALAM IMPROVISASI GITAR JAZZ - Dias Agusta (Saraswati)
ABSTRACT The Application of Melodic Minor Scale in Jazz Guitar Improvisation. Nowadays, guitar is one of important instruments in jazz music. Guitar can have a role as a melody carrier as well as a harmony carrier by its chord. In jazz music, improvisation is an important aspect that have to be learned and played. Player have to understand common techniques that played in a jazz improvisation such as variate melody, play chord tones, color tones, arpeggio, neighboring tones, etc. In jazz music sphere, improvisation using melodic minor scale is a uniqueness. This scale is very well played on dominant chord for creating altered dominant sounds and it also can be played on other chord such as major chord, minor, half-diminished, and diminished. Key words: Jazz, improvisation, guitar, melodic minor scale